Li-ion batteries using electrolytes based on mixtures of poly(vinyl alcohol) and lithium bis(triflouromethane) sulfonamide salt. (20th August 2017) - Ek, Gustav; Jeschull, Fabian; Bowden, Tim; Brandell, Daniel
Abstract: Poly(vinyl alcohol) (PVA) has, to a limited degree, previously been investigated as an alternative host material to the dominating poly(ethylene oxide)-(PEO)-based polymer electrolytes used in electrochemical applications. These PVA-materials were found to be highly ionically conducting for a number of different salts at temperatures below the glass transition temperature, but in the presence of DMSO (dimethyl sulfoxide) residues. Here, we investigate the PVA:LiTFSI (lithium bis(triflouromethane)sulfonamide) electrolytes system, thereby for the first time using the salt most commonly explored in PEO-based systems also in PVA. It is shown that this results in significantly higher conductivities than for alternative Li salts. Comparisons between electrolytes casted in DMSO, H2 O and hot-pressed samples confirm the necessity of solvent residues present in the DMSO casted films for the ionic transport, although no obvious liquid phase is formed. Moreover, we also show the feasibility of PVA-based electrolytes by construction of functional Li-metal | PVA-LiTFSI (DMSO) | LiFePO4 batteries operating at 60 °C, displaying stable capacities of 136 mAh/g LiFePO4 at a rate of C/20.